2016
DOI: 10.4102/sajip.v42i1.1350
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of qualitative research in Psychology, Industrial and Organisational Psychology and Human Resource Management within South Africa: A critical review

Abstract: Orientation: Qualitative research is marked by phenomenal growth and development over the years.Research purpose: This article aims to offer insight into the emerging qualitative methodologies used in the fields of Psychology, Industrial and Organisational Psychology and Human Resource Management.Motivation for the study: The value of qualitative organisational research has been recognised since the 1970s. Regardless of its perceived value, national and international trends show a greater tendency for quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Research has also focused on the use of research methods in specific sub-disciplines of psychology, for example, in the field of Industrial and Organisational psychology Coetzee and Van Zyl ( 2014 ) found that South African publications tend to consist of cross-sectional quantitative research methods with underrepresented longitudinal studies. Qualitative studies were found to make up 21% of the articles published from 1995 to 2015 in a similar study by O'Neil and Koekemoer ( 2016 ). Other methods in health psychology, such as Mixed methods research have also been reportedly growing in popularity (O'Cathain, 2009 ).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Research has also focused on the use of research methods in specific sub-disciplines of psychology, for example, in the field of Industrial and Organisational psychology Coetzee and Van Zyl ( 2014 ) found that South African publications tend to consist of cross-sectional quantitative research methods with underrepresented longitudinal studies. Qualitative studies were found to make up 21% of the articles published from 1995 to 2015 in a similar study by O'Neil and Koekemoer ( 2016 ). Other methods in health psychology, such as Mixed methods research have also been reportedly growing in popularity (O'Cathain, 2009 ).…”
Section: Introductionmentioning
confidence: 74%
“…Additionally, researchers also employ various types of literature reviews to address research questions (Grant and Booth, 2009). According to literature, what research method is used and why a certain research method is used is complex as it depends on various factors that may include paradigm (O'Neil and Koekemoer, 2016), research question (Grix, 2002), or the skill and exposure of the researcher (Nind et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinyamurindi ( 2012) lauds for more qualitative research, especially within the HRM and IOP fields, which is also supported by other scholars (e.g. Harry et al, 2018;Kinnear & Ruggunan, 2019;O'Neil & Koekemoer, 2016) as a useful basis for understanding behaviour, especially when working with vulnerable groups and complex life experiences. We seek to answer such calls and illustrate the value of qualitative research through the use of drawings in HRM employability research.…”
Section: Gaps In the Literaturementioning
confidence: 86%
“…Taking this statement into consideration, the reviewers recommend that future edited versions of Transforming research methods in the social sciences should also consider including more traditional research methods as case studies within the South African context, as there are many examples of these. Further reading suggestions include research articles published by Scholtz et al (2020), Coetzee andVan Zyl (2014) andO'Neil andKoekemoer (2016), which provide a broad overview of the use of research methods internationally and nationally within the psychology research context. Other research books such as Doing social research (Wagner, Kawulich, & Garner, 2012), Research at grass roots (De Vos, Strydom, Fouche, & Delport, 2011), Doing research in the real world (Gray, 2014), First steps in research (Maree, 2016), The practice of social research (Babbie & Mouton, 2001), and Research in practice (Terre Blanche, Durrheim, & Painter, 2006) are also recommended as good reads for students, academia and researchers in practice.…”
mentioning
confidence: 99%